Nomenclatural notes on Brazilian Myrtaceae - Sobral, M.; Souza, M. C.; Mazine-Capelo, F.; Lucas, E. (Phytotaxa, 2014)
Throughout 2009 the Rio de Janeiro Botanical Garden coordinated the production of a checklist of the Brazilian flora. Among involved taxonomists involved in this project, the authors of this paper were invited to work on Myrtaceae. The valid names included in the Brazilian checklist were mostly based on the world checklist of Myrtaceae by Govaerts et al. (2010); nevertheless, advances in our knowledge of Brazilian Myrtaceae, including several unpublished phylogenies, necessitate some routine nomenclatural changes. Such changes—seven new combinations, three new names and fifty-two synonyms are very briefly discussed herein; synonymies are based on comparison of type material, and detailed discussion on each case is mostly avoided. The synonyms included under each species are those directly relevant to the points discussed in this paper; for a complete synonymy the reader is referred to Govaerts et al. (2010). Additional information on geographic and ecologic topics is not provided in order to avoid redundancy with data that will shortly be made available in the Brazilian checklist.